Role of daily anal stimulation for intractable functional constipation in infants. Issue 2 (5th July 2020) - Zhu, Tianqi; Sun, Xiaoyi; Zhu, Dan; You, Qian; Wan, Xiaoting; Meng, Xinyao; Feng, Jiexiong
Abstract : Objective: Functional constipation is one of the most common problems in pediatric gastroenterology. The aim of the present study was to evaluate the effectiveness of daily anal stimulation in infants with intractable functional constipation (IFC). Our evaluation was based on clinical improvement and on changes in manometric parameters through time. Methods: Infants with IFC treated between January 2018 and December 2019 were included in this retrospective study. Treatment processing included daily anal stimulation for infants and psychological counseling for parents. All cases underwent a complete intervention program and were evaluated for improvement in symptoms and for changes in anorectal manometry within 1 year of follow-up. Results: A total of 161 patients were included in this study. Positive response was achieved in all patients. Frequency of defecation, change in stool form and decrease in the defecatory pain were significantly relieved in all infants after intervention. On anorectal manometry, no significant difference was found in the peristaltic frequency of distal rectum before and after treatment. There was a significant increase in the mean amplitude of peristalsis and improvement in the rhythm after intervention. In the 1 year of follow-up, three patients had recurrence of constipation requiring colectomy. Conclusion: In terms of the high clinical efficacy and limited side effects, daily anal stimulation may be included in the initial part of an intervention program for IFC in infants.